Landscapes and mechanisms of CD8+ T cell exhaustion in gastrointestinal cancer - Ding, Jia-Tong; Yang, Kang-Ping; Zhou, Hao-Nan; Huang, Ying-Feng; Li, Hui; Zong, Zhen (Frontiers in Immunology, 2023)
CD8+ T cells, a cytotoxic T lymphocyte, are a key component of the tumor immune system, but they enter a hyporeactive T cell state in long-term chronic inflammation, and how to rescue this depleted state is a key direction of research. Current studies on CD8+ T cell exhaustion have found that the mechanisms responsible for their heterogeneity and differential kinetics may be closely related to transcription factors and epigenetic regulation, which may serve as biomarkers and potential immunotherapeutic targets to guide treatment. Although the importance of T cell exhaustion in tumor immunotherapy cannot be overstated, studies have pointed out that gastric cancer tissues have a better anti-tumor T cell composition compared to other cancer tissues, which may indicate that gastrointestinal cancers have more promising prospects for the development of precision-targeted immunotherapy. Therefore, the present study will focus on the mechanisms involved in the development of CD8+ T cell exhaustion, and then review the landscapes and mechanisms of T cell exhaustion in gastrointestinal cancer as well as clinical applications, which will provide a clear vision for the development of future immunotherapies.